Happy Halloween from the Very Busy Spider : A Lift-The-Flap Book (World of Eric Carle) - Carle, Eric (New York : World of Eric Carle, an imprint of Penguin Random House LLC, 2020)
Lift the flaps to find all of Spiders friends on Halloween.
Cover title.
"A lift-the-flap-book"-- Cover.
new kids book 2024 summer.
Ages 3 and up.
Keywords: Lift-the-flap books -- Specimens; Board books; Stories in rhyme; Spiders -- Fiction; Lift-the-flap books; Toy and movable books; Board books; Halloween -- Fiction; Lift-the-flap books; Toy and movable books